Realizing the Narrative: Higher Education Strategies as Creative Economy Agents in Indonesia - Muh. Syaiful Saehu; Ansori Ansori; Suharto Suharto; Desy Putri Purnamasari; Gallex Simbolon (AL-ISHLAH: Jurnal Pendidikan, 2023)
The development of the creative economy in Indonesia encounters several obstacles, including regulatory issues and government protection, as well as the need for more technological knowledge and innovation owned by business people. Higher education academics, as intellectuals, play an essential role in developing this creative economy, considering that academics are very closely related to science, technology, and research innovation. This article will discuss Indonesia's creative economy and how people perceive it. Furthermore, it will look at the importance of higher education as a printer for young entrepreneurs in the sector. This article examines two aspects of curriculum development based on the creative economy and work placements for young entrepreneurs. It will then demonstrate how young graduates can be empowered to build creative economy careers. This research uses a literature review as the design. Five articles were taken as the data sources for this study. The results of the study show that to create young creative workers, higher education must create a curriculum that is based on the creative economy and is oriented towards; competency-based, facilitating creativity, skills, and talents possessed by students, and there is a balance of soft science and hard science for future tertiary graduates. In the narrative of job placement for young creative workers, every tertiary institution is trying to connect and even be able to create business opportunities in various sectors of the creative economy without looking at the economic and social factors of these young creative workers.